Epidemiological profile and incidence of a suicide victims in Brazil (Research, Society and Development, 2020)
The world health organization (WHO) points out that suicide is one of the three main causes of death in the population between 15 and 44 years old, present in developed and developing countries. The world suicide rate is around 11.5 deaths per 100 thousand inhabitants. Suicide is characterized as a deliberate, conscious and intentional act, through which the individual causes his own death that occurs through a convergence between factors psychological, biological and social problems that represent a major public health problem worldwide. The objective of this study was to analyze the trend of mortality by suicide in Brazilian regions from 2015 to 2018. It is an epidemiological, documentary, retrospective, descriptive, with a quantitative approach on suicide rates in Brazil from 2015 to 2018. Data were obtained from the Information System in the official database of SINAN, from DATASUS. It was possible to show that adults in the age range aged 30 to 39 years have a high rate of suicide deaths in the country, noting that there is a significant proportion among young people aged 15 to 19 years. The male sex stands out for committing more self-extermination than the female sex and in terms of marital status, the single person has a higher rate when compared to the married person. The data obtained reveal that there is an urgent need for preventive measures in relation to suicide, due to the proportions of the number of cases of death in relation to this deliberate act, caused intentionally and voluntarily.